Clinical and therapeutic aspects of menopause. - Di Paola, Guillermo (2015)
We will address the issue, we consider always topical, based on the criteria and concepts developed in the experience in private practice and in the office of climacteric we created in the 1st. Chair of Gynecology and four years ago. In this exhibition we will refer only to some approaches to the problem trying to convey concepts or personal criteria that we have made based on clinical and experimental intense dedication.